Future Perspectives in Percutaneous Treatment of Tricuspid Regurgitation - Mangieri, Antonio; Pagnesi, Matteo; Regazzoli, Damiano; Laricchia, Alessandra; Ho, Edwin; Goldberg, Ythan; Chau, Mei; Gallo, Francesco; Fisicaro, Andrea; Khokhar, Arif; Colombo, Antonio; Giannini, Francesco; et al. (Frontiers in Cardiovascular Medicine, 2020)
Tricuspid regurgitation (TR) has a not negligible prevalence and its severity is correlated with poorer outcomes. However, surgical options are rarely offered to these patients because of their high surgical risk. Given that medical therapy plays a limited role in the management of these patients, there is an increasing clinical need for transcatheter treatment options. Although, transcatheter tricuspid valve interventions (TTVIs) are still at an early stage, emerging data suggests their clinical effectiveness and safety, with preliminary results highlighting the potential benefits of transcatheter treatments over medical therapy. In this review, we highlight the challenges and future directions of current and emerging technologies dedicated to the treatment of TR along with an analysis of the next steps required in future clinical trials and studies dedicated to the treatment of the forgotten valve.